2017
DOI: 10.1016/j.tox.2016.05.020
|View full text |Cite
|
Sign up to set email alerts
|

Recreational use of marijuana during pregnancy and negative gestational and fetal outcomes: An experimental study in mice

Abstract: The prevalence of marijuana use among pregnant women is high. However, the effects on gestation and fetal development are not well known. Epidemiological and experimental studies present conflicting results because of the route of administration, dose, time of exposure, species used, and how Cannabis toxicity is tested (prepared extracts, specific components, or by pyrolysis). In this study, we experimentally investigated the effects of maternal inhalation of Cannabis sativa smoke representing as nearly as pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
68
1
12

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(86 citation statements)
references
References 45 publications
5
68
1
12
Order By: Relevance
“…As far as biological plausibility models are concerned, the active ingredient of marijuana, Δ-9-tetrahydrocannabinol (THC) and its metabolites, appears to play a role in carcinogenesis as it crosses the placenta, accumulates in the developing embryo and may result in adverse gestational and fetal outcomes such as reduced birth weight, as demonstrated in animal models 37. Furthermore, marijuana tar was found to induce higher levels of the carcinogen-metabolising enzyme cytochrome P4501A1 (CYP1A1) messenger RNA (mRNA) 38.…”
Section: Discussionmentioning
confidence: 99%
“…As far as biological plausibility models are concerned, the active ingredient of marijuana, Δ-9-tetrahydrocannabinol (THC) and its metabolites, appears to play a role in carcinogenesis as it crosses the placenta, accumulates in the developing embryo and may result in adverse gestational and fetal outcomes such as reduced birth weight, as demonstrated in animal models 37. Furthermore, marijuana tar was found to induce higher levels of the carcinogen-metabolising enzyme cytochrome P4501A1 (CYP1A1) messenger RNA (mRNA) 38.…”
Section: Discussionmentioning
confidence: 99%
“…While there were significant increases in offspring mortality at both doses, broad-based behavioral testing (including the rest-activity cycle, latency to attach to a nipple and ontogeny of locomotor activity) did not reveal adverse effects of early THC exposure ( Brake et al, 1987; Hutchings et al, 1987, 1989, 1991a, 1991b). In a recent inhalation mouse study, a dose of ~ 0.5 mg/kg/day THC smoke from GD 5.5–17.5 produced deficits in fetal growth and reduced birthweights in cannabis-exposed offspring (Benevenuto et al, 2017). Pups with a history of gestational THC exposure showed a surprising 9.9% drop in birthweight and significant decrements in the weight of lungs, brain, thymus, and liver.…”
Section: Insights From Experimental Work With Preclinical Speciesmentioning
confidence: 99%
“…The use of marijuana during pregnancy could have implications for foetal brain development . Marijuana is lipid soluble and able to cross the placenta and blood‐brain barrier to accumulate in foetal tissues including brain tissues .…”
Section: Introductionmentioning
confidence: 99%
“…The strongest evidence of adverse effects of prenatal marijuana exposure comes from animal studies . These studies demonstrated that even low doses of marijuana during pregnancy can result in adverse cognitive and developmental effects in offspring . In human studies, there are variations in the effect's direction, degree and duration .…”
Section: Introductionmentioning
confidence: 99%